Il posizionamento satellitare compie trent’anni: lo stato dell’arte del GNSS - Bernardini, Fulvio (GEOmedia, 2008)
Satellite Positioning 30th anniversary: GNSS state of the art This year marks the 30th anniversary of the Satellite Positioning system. In 1978 the United States launched the first ever experimental satellite which formed the basis for the first Global Positioning System, commonly referred to as GPS. The system has evolved over the years from strict military use to more commercial mainstream applications. Today GPS is used in varied independent projects in the GNSS universe.